A cross sectional study to determine whether there are central nervous system changes in football players who have sustained recurrent lateral ankle injuries using the laterality judgement task, two point discrimination test and limb perception testing - Jakoet, Rashaad (Department of Health and Rehabilitation Sciences, 2016)
Background: A chronic ankle sprain injury is a condition that affects professional, amateur and social football players globally. Despite a large amount of research into the medical management of this condition, it remains one of the most frequently experienced injuries in professional football. A previous ankle sprain is a recognised risk factor for future lateral ankle sprain injury. No previous study has investigated the effects of chronic lateral ankle sprains on the cortical representation of the ankle in the brain. Aim: To determine if there are any changes in the primary and secondary somatosensory cortices of football players who have a history of recurrent ankle sprain injuries Methods: 25 professional male football players (13 previously injured, 12 noninjured) with an average age of 24.9y (+/- 4.49y) from a national first division club were recruited for the study. . All players included in the study completed an informed consent form before participation in the study and were declared fit to play by the clubs medical staff. Player demographics and training history were collected by means of a questionnaire followed by anthropometric measurements being taken. Tests used in the assessment of complex regional pain syndrome (Laterality Judgement Task recognition, two point discrimination and limb perception drawing) were used to assess for cortical representation changes in both limbs of injured players and uninjured players.